Breastfeeding and Parafunctional Oral Habits in Children With and Without Attention-Deficit/Hyperactivity Disorder - SABUNCUOĞLU, OSMAN TALAT (MARY ANN LIEBERT, INC, 2014)
Introduction: Although children with attention-deficit/hyperactivity disorder (ADHD) were reported to have insufficient breastfeeding, consequences and oropharyngeal implications of this finding have not been studied. In this case-control study, we aimed to investigate early feeding practices and parafunctional oral habits in children with ADHD. Subjects and Methods: The study group consisted of 200 children and adolescents, 7-17 years old, diagnosed as having ADHD at Marmara University Child Psychiatry Clinics in Istanbul, Turkey. The Conners Parent and Teacher Rating Scales were used to assess behavioral disturbances. A questionnaire was developed consisting of items pertaining to breastfeeding period, early feeding history, and parafunctional oral habits. The study data were compared with those for 175 healthy schoolchildren after exclusion of possible ADHD cases. Results: The children with ADHD were found to have insufficient exclusive breastfeeding (less than 6 months) (p = 0.0001). The children with insufficient exclusive breastfeeding were more likely to have a history of bottle feeding, longer duration of bottle feeding, and early introduction of bottle feeding (p = 0.01). Overall, significant differences were detected on the domains of duration of bottle feeding, introduction of bottle feeding, introduction of pacifier use, variables of nail and toenail biting, as well as pencil biting, bruxism, and snoring between the ADHD group and the control group. Conclusions: The present results indicate that early in life, children with ADHD are subject to insufficient exclusive breastfeeding, different feeding practices, and elevated parafunctional oral habits more often than typically developing children. For all professionals who provide healthcare to children, increased awareness and attention to these factors are suggested.
Keywords: DEFICIT HYPERACTIVITY DISORDER; NONNUTRITIVE SUCKING HABITS; DURATION